Prevalence and Associated Risk Factors of Anemia Among Hospitalized Children in a Tertiary Level Hospital in Botswana - Aobakwe Betty Siamisang MMed, FA Paed (SA); Alemayehu M. Gezmu MD; Jeremy S. Slone MD, MPH; Lesego Gabaitiri PhD; Thuso David MMed, Cer Paed Cardiology (SA); Bathusi Phetogo MBBS; Dipesalema Joel MBBChBAO, B Med Sc (NUI) (SAGE Publishing, 2023)
Anemia is a global health concern and has been associated with long term cognitive and behavioral adverse effects. A cross sectional study was conducted to determine the prevalence of and risk factors for anemia in infants and children between 6 months to 5 years of age admitted to a tertiary hospital in Botswana. Baseline full blood count of every patient admitted during the study period was assessed to determine if anemia was present. Data were collected from patient's medical inpatient chart, electronic medical record (Integrated Patient Management System (IPMS)), and through interviewing parents and caregivers. Multivariate logistic regression model was used to identify risk factors of anemia. A total of 250 patients were included in the study. Prevalence of anemia in this cohort was 42.8%. There were 145 (58%) males. Of the patients with anemia, 56.1%, 39.2%, and 4.7% had mild, moderate, and severe anemia, respectively. Microcytic anemia consistent with iron deficiency was identified in 61 (57%) patients. Age was the only independent predictor of anemia. Children aged 24 months and more had a 50% lower risk of having anemia than their younger counterparts (odds ratio (OR) 0.52; 95% Confidence Interval (95% CI) 0.30 to 0.89). The findings of this study demonstrate anemia as a serious health concern in the pediatric population in Botswana.